Diagnostic complex «Bort» - K. V. Kostin; K. S. Kryukov; I. Yu. Lepeshinsky (Омский научный вестник)
The article deals with the issue of checking the operability of electrical equipment of armored vehicles. This issue is relevant, due to the need to maintain constant combat readiness of armored vehicles. The system is saturated with automated and automatic systems for various purposes, while there is a problem of rapid troubleshooting in the operation of devices and electrical equipment systems. Existing diagnostic systems allow testing through diagnostic connectors or with a break in the supply circuit through adapters. The diagnostic complex discussed in the article will allow you to check the operation of consumers, blocks without disconnecting connectors.